Pointless Diversity Training: Unconscious Bias, New Racism and Agency. (February 2018) - Noon, Mike
The latest fashion of 'unconscious bias training' is a diversity intervention based on unproven suppositions and is unlikely to help eliminate racism in the workplace. Knowing about bias does not automatically result in changes in behaviour by managers and employees. Even if 'unconscious bias training' has the theoretical potential to change behaviour, it will depend on the type of racism: symbolic/modern/colour-blind, aversive or blatant. In addition, even if those deemed racist are motivated to change behaviour, structural constraints can militate against pro-diversity actions. Agency is overstated by psychology-inspired 'unconscious bias training' proponents, leading them to assume the desirability and effectiveness of this type of diversity training intervention, but from a critical diversity perspective (sociologically influenced) the training looks pointless.